Escape from Hitler's Europe : an American airman behind enemy lines - Watt, George, 1913-1994 (University Press of Kentucky, 2006)
November 1943: American flyer George Watt parachutes out of his burning warplane and lands in rural Nazi-occupied Belgium. Escape from Hitler's Europe is the incredible story of his getaway--how brave villagers spirited him to Brussels to connect with the Comet Line, a rescue arm of the Belgian resistance. This was a gravely dangerous mission, especially for a Jewish soldier who had fought against Franco in the Spanish Civil War. Watt recounts dodging the Gestapo, entering Paris via the underground, and finally, crossing the treacherous Pyrenees into Spain. In 1985, he returned to Belgium a.